Effects of three different rehabilitation games' interaction on brain activation using functional near-infrared spectroscopy. (28th December 2020) - Wang, Zilin; Liao, Minyan; Li, Qinbiao; Zhang, Yanjie; Liu, Heshan; Fan, Zhijun; Bu, Lingguo
Abstract: Objective : This study reveals the changes in brain activation due to different game interaction states based on functional near-infrared spectroscopy signals and discusses their significance for stroke rehabilitation. Approach : The oxygenated hemoglobin concentration (Delta [HbO2 ]) signals and the deoxygenated hemoglobin (Delta [HbR]) signals were recorded from the prefrontal cortex (PFC), the motor cortex (MC), the occipital lobe (OL) and the temporal lobe of 21 subjects (mean age: 24.6 ± 1.9 years old) in three game interaction states: physical, motion-sensing, and button-push training. The subjects were also asked to complete user-satisfaction survey scales after the experiment. Main results : Compared with the button-training state, several channels in the PFC and MC region of the physical-training state were significantly altered as were several channels in the RMC region of the motion-sensing training state ( P < 0.05 after adjustment). The motion-sensing state of the PFC had a significant correlation with that of the MC and the OL. The subjective scale results show that the acceptability of the physical and motion-sensing states was greater than the acceptability of the button-push training state. Significance : The results show that the brain regions responded more strongly when activated by the physical and motion-sensing states compared with the button-push training state, and the physical and motion-sensing states are more conducive to the rehabilitation of the nervous system. The design of rehabilitation products for stroke patients is discussed and valuable insights are offered to support the selection of better interactive training methods.